The Effect Recombinant Growth Hormone (rGH) Doses and ImmersionDuration on Growth Rate and Survival of Gouramy FishLarvae (Osphronemus gouramy) - Surya Aji Ramadana; Netti Aryani; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe aim of this research was to determine the effect ofRecombinant Growth Hormone (rGH) Doses and immersion duration on Growth Rate and Survival of giant gouramy Larvae (Osphronemus gouramy).The research was conducted from December 2019 to February 2020 at the Fish Hatcheryand Breeding Laboratory, Faculty of Fisheries and Marine Riau University. The method used was aComplete Randomized Design (RAL) with 2 factors. The first factor was the dose of rGH with 3 levels;0 mg/l (D0), 2 mg/l (D1), and 3 mg/l (D2). While the second factor was the immersion durationwith three levels of 45 minutes (P1), 60 minutes (P2) and 75 minutes (P3) respectively. TheLarvae were culturedin aquariumfilled with 15 litersof ground waterfor 40 days. The results showed that the use of different doses and immersion duration of rGH effected on absolute weight, absolute length, specific growth rate and survival of giant gouramy larvae. Treatment dose 3 mg /l and 60 minutes (D2P2) with the result of absolute weight growth of 1.20 grams, absolute length 3.48 cm, specific growth rate of 14.61 % and for sincerity with a value of 100.00%. The water quality parameters during the study were optimal for gourami larvae namely water temperature 27.8-28.9 0C, pH 5.9-6.9 and dissolved oxygen 3.5-6.8 mg/l.Keywords : Different Doses, Immersion Duration,rGH, Gouramy fish Larvae,Growth and Survival rate